2011
DOI: 10.1007/s11103-011-9797-6
|View full text |Cite
|
Sign up to set email alerts
|

Chloroplast β chaperonins from A. thaliana function with endogenous cpn10 homologs in vitro

Abstract: The involvement of type I chaperonins in bacterial and organellar protein folding has been well-documented. In E. coli and mitochondria, these ubiquitous and highly conserved proteins form chaperonin oligomers of identical 60 kDa subunits (cpn60), while in chloroplasts, two distinct cpn60 α and β subunit types co-exist together. The primary sequence of α and β subunits is ~50% identical, similar to their respective homologies to the bacterial GroEL. Moreover, the A. thaliana genome contains two α and four β ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 31 publications
1
34
0
Order By: Relevance
“…Cpn60α2 (At2g28000) cloning and purification was based on the Cpn60β2 method [11] with the following adaptation: Cpn60α2 was cloned between the BamHI-NotI sites of the modified version of pET21d+ which codes for an octa-histidine tag followed by the TEV (Tobacco Etch virus) proteolysis site at the amino terminus of the protein [22]. The first amino acid of the mature protein was chosen to be alanine 46 and it contained an additional glycine-serine at the N-terminus.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cpn60α2 (At2g28000) cloning and purification was based on the Cpn60β2 method [11] with the following adaptation: Cpn60α2 was cloned between the BamHI-NotI sites of the modified version of pET21d+ which codes for an octa-histidine tag followed by the TEV (Tobacco Etch virus) proteolysis site at the amino terminus of the protein [22]. The first amino acid of the mature protein was chosen to be alanine 46 and it contained an additional glycine-serine at the N-terminus.…”
Section: Methodsmentioning
confidence: 99%
“…3) Both chaperonin and co-chaperonin subunits can assemble into a variety of functional homo- and hetero-oligomeric complexes. Cpn60αβ hetero-oligomer is the most abundant oligomeric form in vivo (reviewed in [10]), although the Cpn60β subunits were shown to be functional as homo-oligomers in vitro [11]. In terms of co-chaperonins, Cpn10 and Cpn20 can function in vitro as heptameric and tetrameric homo-oligomers, respectively [12][15].…”
Section: Introductionmentioning
confidence: 99%
“…The subunit arrangement in the chloroplast chaperonin is still unknown (11). Both native (12) and recombinant (13)(14)(15) plant chloroplast chaperonins have been characterized biochemically and shown to assist protein folding in vitro. Recently, it has been shown that the low abundance chaperonin subunit Cpn60␤4 is specifically required to fold the chloroplast protein NdhH, suggesting that substrate specificity may exist in vivo based on the subunit composition of the chaperonin (16).…”
mentioning
confidence: 99%
“…This may be due to minor variations in amino acids of the apical domain of Cpn60, which makes contact with the co-chaperonin and substrate protein. The results of this study suggested that chloroplasts may contain active Cpn60b homo-oligomers in addition to hetero-oligomers, reflecting various cellular roles [37].…”
Section: Box 1 Arabidopsis Chaperonin Familymentioning
confidence: 71%